Application Of Synthesised Zeolite A From Kankara Kaolin For Solar Adsorption Refrigeration - Amber, I.; Folayan, Clement; Suleiman, Rekiyah; Yusuf Atta, Abdulazeez (Journal of Mechanical Engineering and Technology (JMET), 2013)
This paper presents the synthesis, characterization and application of a synthesised Zeolite A from Nigerian clay (kankara) for application in solar adsorption refrigeration. On the basis of X-ray diffraction, TGA and DTA experiments Zeolite A was confirmed with and adsorption capacity of 0.3 kgadsorbate/0.85 kg adsorbent, regenerative temperature of below 200oC and structural stability below 800oC.The refrigeration system used in the test consists of a 0.6 by 0.45 m2 parabolic trough concentrator, 0.6 m long and 0.25 m diameter black coated absorber, an air cooled condenser and cooling box of volume(evaporator) 0.048 m3. The refrigerator was constructed and tested at the Mechanical Engineering Department Zaria, Nigeria at location 11.11’NE in the month of April, a month with one of the highest of average solar irradiation of 900W/ m2. The lowest evaporator temperature attained was 9.8°C with a C.O.P of 28.5%.